Hepatoprotective Effect of Rimonabant Against Isoniazid Induced Liver Damage In Albino Wistar Rats - Noorani, Arshad Ali (International Journal of Pharmaceutical & Biological Archive, 2011)
The present study was conducted to evaluate the hepatoprotective activity of the rimonabant against isoniazid-induced liver damage in albino wistar rats. Hepatotoxicity was induced by daily dose of isoniazid (250mg/kg p.o.) for 14 days as manifested by statistically significant increase in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and bilirubin level. Pretreatment of rats with the rimonabant at doses of 2.5, 5 and 10 mg/kg prior to isoniazid dosing at 250mg/kg p.o statistically lowered the serum liver enzyme activities. The activity of the rimonabant was comparable to the standard drug, silymarin (50mg/kg, p.o.). Results obtained from histopathological studies also supported hepatoprotective activity against ethanol-induced hepatotoxicity. Thus the study demonstrates that rimonabant possess antihepatotoxic effect against isoniazid.